Exploring Consumer Behavior in Indonesian Online Marketplaces - Zulkifli, Zulkifli; Rachbini, Widarto; Agustina, Anna; Fathoni, Muhammad Anwar; Fitriningrum, Andriati (International Review of Management and Marketing, 2024)
The burgeoning landscape of online marketplaces in Indonesia has prompted an exploration into the intricate interplay between consumer browsing behaviors and their impact on e-satisfaction, electronic word-of-mouth (e-WOM), and repurchase intention. This study investigates these relationships within Indonesian online marketplaces, employing a robust quantitative methodology. Surveys were conducted with 962 users of Indonesian online markets, and data was analyzed using SPSS 29 and Smart PLS 3. Findings reveal significant associations between utilitarian browsing and both e-satisfaction and repurchase intention. Hedonic browsing also significantly influences e-satisfaction, though its impact on e-WOM is less pronounced. E-satisfaction emerges as a critical precursor to both repurchase intention and e-WOM, underscoring its pivotal role in shaping consumer behavior within online marketplaces. Practical implications suggest businesses in Indonesian online marketplaces should adopt a multifaceted approach to platform design, prioritizing user satisfaction and transactional efficiency. Proactive customer satisfaction initiatives, coupled with leveraging satisfied customers as brand advocates, are essential for fostering long-term loyalty and advocacy. Theoretical contributions refine existing models in e-commerce and marketing, emphasizing the dynamic nature of online consumer behavior and its implications for managerial decision-making. While the study provides valuable insights, acknowledging its limitations underscores the need for future research. Longitudinal studies, qualitative approaches, and comparative analyses across cultural contexts are recommended to further explore online consumer behavior in Indonesian marketplaces and beyond. This research contributes to both scholarly understanding and managerial practices in the dynamic realm of online retail.